2010
DOI: 10.1120/jacmp.v11i1.2947
|View full text |Cite
|
Sign up to set email alerts
|

Percentage depth dose evaluation in heterogeneous media using thermoluminescent dosimetry

Abstract: The purpose of this study is to investigate the influence of lung heterogeneity inside a soft tissue phantom on percentage depth dose (PDD). PDD curves were obtained experimentally using LiF:Mg,Ti (TLD‐100) thermoluminescent detectors and applying Eclipse treatment planning system algorithms Batho, modified Batho (M‐Batho or BMod), equivalent TAR (E‐TAR or EQTAR), and anisotropic analytical algorithm (AAA) for a 15 MV photon beam and field sizes of 1×1,.2em2×2,.2em5×5, and 10×10.2emcm2. Monte Carlo simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 24 publications
4
29
0
Order By: Relevance
“…[17] In a similar study by da Rosa et al, they compared the accuracy of different inhomogeneity correction methods in a lung phantom. [13] Analyzing their pertinent data on the MC and the curves without correction revealed that the dose reduction inside the lung at the depth 10 cm (the comparable depth with our results, 5 cm distance from interface) was 50% and 90% respectively for 2 cm × 2 cm and 1 cm × 1 cm field sizes respectively for 15 MV photon beam. Comparing to our results of 46% and 70% for the same field sizes, the differences were acceptable with consideration of differences in used MC code, geometries, and photon beams energies.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…[17] In a similar study by da Rosa et al, they compared the accuracy of different inhomogeneity correction methods in a lung phantom. [13] Analyzing their pertinent data on the MC and the curves without correction revealed that the dose reduction inside the lung at the depth 10 cm (the comparable depth with our results, 5 cm distance from interface) was 50% and 90% respectively for 2 cm × 2 cm and 1 cm × 1 cm field sizes respectively for 15 MV photon beam. Comparing to our results of 46% and 70% for the same field sizes, the differences were acceptable with consideration of differences in used MC code, geometries, and photon beams energies.…”
Section: Discussionsupporting
confidence: 61%
“…While, the other algorithms were not capable to predict the lung dose accurately in the conditions of electronic disequilibrium with high energy photons. [3,13,14] Otherwise, the presence of small sold lung tumor would make more difficult situation for TPSs to predict the dose inside the tumor. To address these issues we planned a MC study for depth dose variations in the lung with and without a small tumor resembling the situations occur in IMRT of lung tumors.…”
Section: Introductionmentioning
confidence: 99%
“…by van Esch [4], Fogliata [2], daRosa [5]. Results showed that accuracy significantly depends on energy, field size, and density of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…The dosimetric accuracy of complex RapidArc plans which are associated with more small MLC segments was also investigated. As the accuracy of AAA is expected to decrease in low density media, 8,18 we also compared dose calculations for a typical RapidArc plan for lung stereotactic body radiotherapy (SBRT) with measurements in different heterogeneous phantoms, and evaluated the actual dosimetric implications.…”
Section: Introductionmentioning
confidence: 99%